2012
DOI: 10.1136/jech-2012-201537
|View full text |Cite
|
Sign up to set email alerts
|

Urban neighbourhood unemployment history and depressive symptoms over time among late middle age and older adults

Abstract: Background Little is known about how a neighbourhood’s unemployment history may set the stage for depressive symptomatology. This study examines the effects of urban neighbourhood unemployment history on current depressive symptoms and subsequent symptom trajectories among residentially stable late middle age and older adults. Contingent effects between neighbourhood unemployment and individual-level employment status (ie, cross-level interactions) are also assessed. Methods Individual-level survey data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Neighborhood-level factors were operationalized at the Census tract level, which is a common approach in health research (Wight et al, Forthcoming). We draw our neighborhood-level data from the American Community Survey (ACS) 2006–2010 five-year estimates (US Census Burean, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Neighborhood-level factors were operationalized at the Census tract level, which is a common approach in health research (Wight et al, Forthcoming). We draw our neighborhood-level data from the American Community Survey (ACS) 2006–2010 five-year estimates (US Census Burean, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Also, depressive symptoms are highest among those residing in neighborhoods characterized by high historical unemployment (Wight et al, 2013). A limited number of studies have examined the relationship between socioeconomic conditions and perceived racial discrimination.…”
Section: The Neighborhood Environmentmentioning
confidence: 99%
“…34 Another study using neighborhood unemployment rates as the exposure of interest found that even those who remain employed report more depressive symptoms. 114 If confirmed, such results would merit close attention by policy makers given that remaining workers generally represent the largest and healthiest portion of the population.…”
Section: Unemployment Vs Recessions Vs Downsizingmentioning
confidence: 99%